P5-S5.01 Factors associated with stated willingness to accept expedited partner therapy from sex partners, NYC, 2007–2008. (10th July 2011) - Sanchez, D; Ricchetti-Masterson, K L; Handel, S; Rogers, M; Schillinger, J A
Abstract : Background: Expedited Partner Therapy (EPT) is a partner management strategy that relies upon index patients to deliver STD treatment to their sex partners without an evaluation by a healthcare provider. Characterisation of barriers and facilitators of EPT acceptance could inform approaches to EPT implementation. The New York City (NYC) Bureau of STD Control is in the process of implementing EPT and is offering technical assistance on EPT to healthcare providers throughout the city. Methods: During 2007–2008, we used a self-administered survey to assess factors associated with hypothetical willingness to accept EPT from an index patient among adults attending two NYC STD clinics. Binomial regression was used to estimate prevalence ratios (PRs) between select survey items and hypothetical willingness to accept EPT from their most recent sex partner, as measured by the question "If your most recent sex partner brought you medicine to treat an STD, would you take it?" Results: Among 658 respondents, median age was 25 (range 14–68); 338 (51.4%) were male. Almost half (42.7%) reported willingness to accept EPT from their most recent sex partner. We examined the association between patient sex, history of chlamydia (CT)/gonorrhoea (GC), last sexual partner type, number of sex partners in past 3 months, and age, with willingness to accept EPT from most recent sex partner. Those willing to accept EPT from their most recent sex partner were more likely to be male (PR=1.14 95% CI 1.00 to 1.31), more likely to have a history of CT/GC (PR=1.28; 95% CI 1.07 to 1.52), and more likely to report 1–2 sex partners in the past 3 months (PR=1.04; 95% CI 0.88 to 1.22). Respondents whose most recent sex partner was a steady partner were more likely to accept EPT (PR=1.09; 95% CI 0.95 to 1.26). Age was not associated with willingness to accept EPT. Only sex and history of CT/GC were significantly associated with willingness to accept EPT in crude analyses (p=0.006, and p=0.05, respectively) see Abstract P5-S5.01 table 1 . Conclusions: Aside from partner's sex, we did not identify any patient characteristics which could be used to predict sex partners' willingness to take medication offered via EPT. Active follow-up with partners given EPT will provide a more direct measure of the acceptability and utilisation of medication delivered to sex partners.